Revision of Eupyrochroa Blair, 1914 (Coleoptera: Pyrochroidae) based on morphological comparison and molecular phylogenetics - Gao, Qi; Young, Daniel K.; Zhan, Zhi-Hong; Cheng, Hai-Yun; Pan, Zhao (Zootaxa, 2024)
Eupyrochroa Blair, 1914 is a small genus of fire-colored beetles (Coleoptera: Pyrochroidae) with two putative species recorded from limited historical distributions in China. The two species, E. insignita (Fairmaire, 1894) and E. limbaticollis (Pic, 1909), have been distinguished on the basis of color differences in the pronotum and scutellum, characters now known to exhibit significant variability. In the present study, adult morphology of the two species was compared, and partial fragments of cytochrome c oxidase subunit I (COI) from 36 samples representing 14 pyrochroid species were obtained by extraction and a GenBank search. Nucleotide composition, genetic distance, and phylogeny were analyzed. The results of morphological and molecular analyses indicate consistency, suggesting that the two “species” are indistinguishable by any significant measure. Therefore, Eupyrochroa limbaticollis (Pic, 1909) is proposed as a junior synonym of E. insignita (Fairmaire, 1894). The species is also redescribed and illustrated, including both adults and larvae.